CURRENCY INDEX AND ITS RELATIONSHIP WITH THE LEVEL OF COUNTRY’S DEVELOPMENT - ANATOLII ZADOI; OLEKSANDR ZADOIA (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
The vast majority of foreign operations are serviced by currency. The exchange rate of the national currency has a significant impact on both the terms of foreign trade and the international movement of capital. For a more accurate assessment of the impact of the exchange rate on foreign economic activity, it is advisable to use the currency index as the ratio of the market (official) exchange rate to purchasing power parity. The aim of our study is to establish the relationship between the level of development of the country and the currency index (including quantitative), as well as the rationale for approaches to the choice of foreign trade partners based on the currency indices. As a factorial basis for the study, statistics in 130 countries of the world were used. In the analysis of the results, a hypothesis about the existence of the relationship between the level of development of the country (which was determined by GDP per capita) and the index of the currency index was put forward. The hypothesis test was conducted using correlation and regression analysis. The indicator of R2 was used as the criterion of connection density. The research was carried out both in the whole array of countries, and for individual groups. The analysis showed a fairly close relationship between the currency index and the level of country development (which is reflected in the high value of the coefficient of determination). Even the unification of countries into economic unions and the transition to duty-free trade does not eliminate the differentiation of the price level and, accordingly, differences in the currency index. This is confirmed by the analysis of the calculated in the article currency index for the EU. And even the use of a single currency in the euro area does not eliminate this problem.